2014
DOI: 10.5303/jkas.2014.47.6.259
|View full text |Cite
|
Sign up to set email alerts
|

G192.8-1.1: A Candidate of an Evolved Thermal Composite Supernova Remnant Reignited by Nearby Massive Stars

Abstract: G192.8¡1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In this version of the catalogue five objects previously listed as SNRs have been removed, namely (G20.4+0.1, G21.5−0.1, G23.6+0.3, G59.8+1.2 and G65.8−0.5, as they have been identified as H regions by Anderson et al (2017). Also, G192.8−1.1 has been removed, as Gao et al (2011) had shown that this is not a SNR (see also Kang, Koo, & Byun 2014). Erroneously it was not removed from the 2014 version of the catalogue.…”
Section: Snrs Added To/objects Removed From the Cataloguementioning
confidence: 99%
“…In this version of the catalogue five objects previously listed as SNRs have been removed, namely (G20.4+0.1, G21.5−0.1, G23.6+0.3, G59.8+1.2 and G65.8−0.5, as they have been identified as H regions by Anderson et al (2017). Also, G192.8−1.1 has been removed, as Gao et al (2011) had shown that this is not a SNR (see also Kang, Koo, & Byun 2014). Erroneously it was not removed from the 2014 version of the catalogue.…”
Section: Snrs Added To/objects Removed From the Cataloguementioning
confidence: 99%